Safety and Immunogenicity from a Phase I Trial of Inactivated Severe Acute Respiratory Syndrome Coronavirus Vaccine - Lin, Jiang-Tao; Zhang, Jian-San; Su, Nan; Xu, Jian-Guo; Wang, Nan; Chen, Jiang-Ting; Chen, Xin; Liu, Yu-Xuan; Gao, Hong; Jia, Yu-Ping; Liu, Yan; Sun, Rui-Hua; et al. (Antiviral therapy, 2007)
Emergence of severe acute respiratory syndrome (SARS) from the winter of 2002 to the spring of 2003 has caused a serious threat to public health. To evaluate the safety and immunogenicity of the inactivated SARS coronavirus (SARS-CoV) vaccine, 36 subjects received two doses of 16 SARS-CoV units (SU) or 32 SU inactivated SARS-CoV vaccine, or placebo control. On day 42, the seroconversion reached 100% for both vaccine groups. On day 56, 100% of participants in the group receiving 16 SU and 91.1% in the group receiving 32 SU had seroconverted. The geometric mean titre of neutralizing antibody peaked 2 weeks after the second vaccination, but decreased 4 weeks later. The inactivated vaccine was safe and well tolerated and can elicit SARS-CoV-specific neutralizing antibodies.